Studying labor market institutions in the lab: minimum wages, employment protection and workfare - Armin Falk; David Huffman (Institute for the Study of Labor (IZA), 2006)
A central concern in economics is to understand the interplay between institutions and labor markets. In this paper we argue that laboratory experiments are a powerful tool for studying labor market institutions. One of the most important advantages is the ability to implement truly exogenous institutional change, in order to make clear causal inferences. We exemplify the usefulness of lab experiments by surveying evidence from three studies, each of which investigates a different, crucial labor market institution: minimum wage laws, employment protection legislation and workfare
Keywords: 330; Mindestlohn; Kündigungsschutz; Aktivierende Sozialhilfe; Arbeitsverwaltung; Test